A transplantable TH‐MYCN transgenic tumor model in C57Bl/6 mice for preclinical immunological studies in neuroblastoma. Issue 6 (14th September 2013) - Kroesen, Michiel; Nierkens, Stefan; Ansems, Marleen; Wassink, Melissa; Orentas, Rimas J.; Boon, Louis; den, Martijn H.; Hoogerbrugge, Peter M.; Adema, Gosse J.
<x xml:space="preserve">Abstract</x> Current multimodal treatments for patients with neuroblastoma (NBL), including anti‐disialoganglioside (GD2) monoclonal antibody (mAb) based immunotherapy, result in a favorable outcome in around only half of the patients with advanced disease. To improve this, novel immunocombinational strategies need to be developed and tested in autologous preclinical NBL models. A genetically well‐explored autologous mouse model for NBL is the TH‐MYCN model. However, the immunobiology of the TH‐MYCN model remains largely unexplored. We developed a mouse model using a transplantable TH‐MYCN cell line in syngeneic C57Bl/6 mice and characterized the immunobiology of this model. In this report, we show the relevance and opportunities of this model to study immunotherapy for human NBL. Similar to human NBL cells, syngeneic TH‐MYCN‐derived 9464D cells endogenously express the tumor antigen GD2 and low levels of MHC Class I. The presence of the adaptive immune system had little or no influence on tumor growth, showing the low immunogenicity of the NBL cells. In contrast, depletion of NK1.1+ cells resulted in enhanced tumor outgrowth in both wild‐type and Rag1−/− mice, showing an important role for NK cells in the natural anti‐NBL immune response. Analysis of the tumor infiltrating leukocytes ex vivo revealed the presence of both tumor associated myeloid cells and T regulatory cells, thus mimicking human NBL tumors. Finally, anti‐GD2 mAb mediated NBL therapy resulted in ADCC in vitro and delayed tumor outgrowth in vivo. We conclude that the transplantable TH‐MYCN model represents a relevant model for the development of novel immunocombinatorial approaches for NBL patients.